UJI TOKSISITAS (brine shrimp lethality test) DAN PENENTUAN AKTIVITAS ANTIOKSIDAN ALAMI DARI DAUN TERAP (ArtocarpusodoratissimusB.) DENGAN METODE DPPH (2,2-diphenyl-1-picrylhidrazyl) - Tri Wahyu Septiani; Erwin - (PROSIDING SEMINAR KIMIA, 2013)
The phytochemical test, brine shrimp lethality test and antioxidant activity test on secondary metabolits of terap (Artocarpus odoratissimus B.)leaves have been completed. The leaves samples are extracted by masseration method that is concentrated by using rotary evaporator. The total extract are fractioned with n-hexane and ethyl acetate. Based on secondary metabolits phytochemical test of terap (Artocarpus odoratissimus B.)leaves showed that total extract, n-hexane fraction extract andEthyl Acetat fraction extractcontains steroid and flavonoid. In brine shrimp lethality test, the increase larvae death data was recorded and processed using SAS Probit Analysis to determine the Lethal Concentration 50 % (LC 50 ) value. The results of this test showed that the most active extract is metanol extract with LC 50 value of 110,5176ppm. Based on the antioxidant activity by scavenging activity of DPPH used spectrophotometry was obtained that Inhibition Concentration 50% (IC 50 ) of total extract is 563,57 ppm, extract of n-hexane fraction is 631,87 ppm and extract of ethyl acetat fraction is 45,30 ppm.